Makna Profesi Barista sebagai Personal Branding pada Generasi Z - Irgiana Fajri Andjani; Ferry Darmawan (Bandung Conference Series: Public Relations, 2023)
Abstract. The development of coffee in Indonesia has been very rapid, because coffee is one of the plantation commodities sold on the world market. With the development of coffee in Indonesia, the consumption of coffee and coffee shops in Indonesia has also increased, this shows the growth of new professional fields that are increasingly popular among Generation Z in the city of Bandung, one of which is becoming a Barista. Generation Z grew up in the digital era and has unique characteristics in building their identity. The Barista profession is an attractive career choice for generation Z, as it provides an opportunity to express their creativity, expertise and interest in the fast-growing world of coffee. The purpose of this research is to find out the motives, meanings, and personal branding formed in Generation Z who work as Baristas. This study uses a qualitative research method with a phenomenological approach. Thus, researchers here are trying to unravel the various existing phenomena by way of in-depth interviews, observation and documentation selected as data collection techniques. The phenomenon of the rise of the Barista profession, which is of great interest to Generation Z, is studied using the theory of self-identity along with Alfred Schutz's phenomenological approach in the hope of being able to analyze data and information about this phenomenon more deeply. The results of the study show that informants as generation Z have several motives, namely motives for forming self-confidence, increasing experience, and increasing self-existence. The Barista profession is also interpreted as a positive trend for informants so that the personal branding that is formed gives an image as a barista who has different characteristics and characteristics. Abstrak. Perkembangan kopi di Indonesia sudah sangat pesat, karena kopi sudah termasuk salah satu komoditas perkebunan yang dijual ke pasar dunia. Dengan berkembangnya kopi di Indonesia, maka meningkat pula konsumsi kopi dan kedai kopi di Indonesia, hal ini menunjukan tumbuh bidang profesi baru yang kian digemari di kalangan Generasi Z di Kota Bandung salah satunya menjadi seorang Barista. Generasi Z tumbuh dalam era digital dan memiliki karakteristik yang unik dalam membangun identitas mereka. Profesi Barista menjadi salah satu pilihan karir yang menarik bagi generasi Z, karena memberikan peluang untuk mengungkapkan kreativitas,keahlian, dan minat mereka di dunia kopi yang berkembang pesat. Tujuan penelitian ini untuk mengetahui Motif, Makna, dan personal branding yang terbentuk pada Generasi Z yang bekerja menjadi seorang Barista. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan fenomenologi. Dengan demikian, peneliti disini berusaha untuk mengurai berbagai fenomena yang ada dengan cara, Wawancara yang mendalam, Observasi dan Dokumentasi dipilih sebagai Teknik pengumpulan data. Fenomena maraknya profesi Barista yang diminati banyak Generasi Z ini dikaji menggukan teori identitas diri bersama pendekatan fenomenologi Alfred Schutz dengan harapan dapat mengurai data dan informasi mengenai fenomena tersebut lebih mendalam. Hasil penelitian menunjukan informan selaku generasi Z memiliki beberapa motif yaitu motif membentuk kepercayaan diri, menambah pengalaman, dan meningkatkan eksistensi diri. Profesi Barista ini juga di maknai sebagai tren yang positif bagi para informan sehingga personal branding yang terbentuk memberikan image sebagai barista yang memiliki ciri khas dan karakteristik yang berbeda-beda.